Star‐Shaped Push‐Pull Molecules with a Varied Number of Peripheral Acceptors: An Insight into Their Optoelectronic Features. Issue 6 (14th April 2018) - Klikar, Milan; Seintis, Kostas; Polyzos, Ioannis; Pytela, Oldřich; Mikysek, Tomáš; Almonasy, Numan; Fakis, Mihalis; Bureš, Filip
Abstract: Star‐shaped molecules with a gradually varied number of peripheral acceptors were designed, synthesized, and subsequently investigated by using differential scanning calorimetry, electrochemistry, and linear absorption and emission spectra. Two‐photon absorption properties were studied by two‐photon absorption fluorescence. Experimental data were completed by the results of quantum chemical calculations and thorough structure‐property relationships were elucidated. The performed analysis showed that structural features such as the number of CN groups, star‐shaped arrangement, π‐linker composition, and multipodality are the most important factors affecting optoelectronic features of the studied chromophores. Abstract : Pushing limits : Fundamental structure‐property relationships in tripodal chromophores are disclosed. The (non)linear optical properties of centrifugal push‐pull molecules based on a popular triphenylamine central donor with a varied number of peripheral acceptors are discussed.